Collaborative Strategic Reading in Teaching Narrative Text in MTs Pembangunan Kuningan - Atla, Vany Septiyanti Putri; Winarto, Eline Rozaliya (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
The objective of this research is to find out the implementation of collaborative strategic reading (CSR) in teaching narrative text at MTs Pembangunan. CSR is a teaching approach that integrates reading strategies with group collaboration to improve text understanding skills. The study involved students from several classes at the high school level who were given CSR training in the context of reading narrative texts. The method used in this research is the qualitative-descriptive method. The results of the research show that the implementation of CSR significantly improves students reading comprehension. In addition, students showed higher involvement and motivation in reading narrative texts through CSR methods compared to traditional methods. The findings indicate that the implementation of CSR carried out by English teachers is relevant to the theory by Klinger and Vaughn (1996) regarding the steps in CSR strategies.